Uzun süreli mevsimsel alerjik konjonktivit tedavisi alan pediatrik olgularda göz içi basıncı değerlendirmesi - Tanrıverdi, Cafer; Demirci, Göktuğ; Karaman Erdur, Sevil; Balcı, Özlem; Özsütçü, Mustafa; Aras, Cengiz; Nurözler Tabakçı, Burcu (My University, 2021)
Amaç: Mevsimsel alerjik konjonktivit (MAK) tanısı ile takip ve tedavi edilen pediatrik yaş grubu hastalarda, dönemsel olarak kullanılan ilaçların uzun dönemde göz içi basıncı (GİB) üzerine olan etkisini araştırmak. Gereç ve Yöntemler: Çalışmaya 16 yaş altında, 5 yıl veya daha fazla süredir MAK tedavisi alan 230 olgu (Grup I) ve kontrol grubuna 16 yaş altında sağlıklı 255 olgu (Grup II) dahil edildi. Hastaların GİB ölçümleri non-kontakt tonometri ile yapıldı. Her iki grubun ortalama GİB değerleri istatistiksel olarak kıyaslandı. Bulgular: Çalışmaya alınan olguların yaş ortalaması grup I'de 9.3±2.0, grup II'de 9.1±2.1 bulundu. Grup I'de hastaların MAK nedeni ile tedavi aldıkları süre ortalama 5.3±0.7 yıldı. Grup I'de ortalama GİB sağ gözde 13.7±3.1 mmHg, sol gözde 13.7±2.8 mmHg bulunurken, grup II'de ortalama GİB sağ gözde 13.8±3.1 mmHg, sol gözde 13.9±3.0 mmHg olarak bulundu. İki grubun ortalama GİB değerleri arasında istatistiksel olarak anlamlı fark olmadığı görüldü (P>0.05). Grup I'de 11 hastada (% 4.8) tedavi esnasında kortikosteroid kullanımına bağlı geçici GİB yükselmesi olduğu gözlendi. Bu hastaların tümünde kortikosteroid kesildikten sonra GİB normale döndü. Sonuç: Pediatrik olgularda MAK tanısıyla dönemsel olarak verilen medikal tedavinin uzun dönemde GİB üzerine kalıcı bir etkisinin olmadığı görüldü. Bu hastalarda olası akut GİB yükselmesini fark etmek için yakın takibin önemli olduğunu düşünmekteyiz.

Objective: To investigate the effect of seasonal drugs on intraocular pressure (IOP) in the long term in pediatric age group who are followed up and treated with seasonal allergic conjunctivitis (SAC) diagnosis. Materials and Methods: The study included 230 cases under the age of 16 who received SAC treatment for 5 years or more (Group I), and 255 healthy cases under the age of 16 in the control group (Group II). IOP measurements of the patients were made with non-contact tonometry. Mean IOP values of both groups were statistically compared. Results: The mean age of the patients included in the study was 9.3±2.0 in group I and 9.1±2.1 in group II. The mean duration of treatment in SAC patients was 5.3±0.7 years. In group I, the mean IOP was 13.7±3.1 mmHg in the right eye, 13.7±2.8 mmHg in the left eye, while in group II the mean IOP was 13.8±3.1 mmHg in the right eye and 13.9±3.0 mmHg in the left eye. There was no statistically significant difference between the mean IOP values of two groups (P>0.05). Temporary IOP elevation due to corticosteroid treatment was observed in 11 patients (4.8%) in group I. In all these patients, IOP lowered to normal limits after corticosteroid treatment discontinued. Conclusion: It was observed that medical treatment, which is given periodically with the diagnosis of SAC in pediatric cases, does not have a permanent effect on IOP in the long term. We think that close follow-up is important to realize possible acute IOP elevation in these patients.
Intraocular pressure assessment in pediatric cases receiving long-term seasonal allergic conjunctivitis treatment
Keywords: Alerjik Konjonktivit; Göz İçi Basıncı; Çocuk; Allergic Conjunctivitis; Intraocular Pressure; Child